Application for Breaking Dormance and Giving Bokashi Salak Steel on the Growth of Salak (Salacca Sumatrana) Seeds - Eka, Eka nurwani ritonga (Jurnal Online Pertanian Tropik, 2021)
The purpose of this study was to determine the effect of breaking dormancy and giving bokashi bark leaves on the growth of salak ( Salacca Sumatrana ) seedlings. This study used a factorial randomized block design (RBD) with 3 blocks (replications). For the factor is the act of breaking dormancy and giving bokashi bark midrib. The statistical results showed that the treatment of dormancy breaking action had a significant effect, on the treatment of leaf area and plant height, the statistical results on the application of salak plant bokashi fertilizer did not show a significant effect on plant height and leaf area. Â